The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41419-020-02885-0
|View full text |Cite
|
Sign up to set email alerts
|

Dual targeting of NUAK1 and ULK1 using the multitargeted inhibitor MRT68921 exerts potent antitumor activities

Abstract: Utilizing oxidative stress has recently been regarded as a potential strategy for tumor therapy. The NUAK family SNF1like kinase 1 (NUAK1) is a critical component of the antioxidant defense system and is necessary for the survival of tumors. Therefore, NUAK1 is considered an attractive therapeutic target in cancer. However, antioxidant therapy induced elevated ROS levels to activate the Unc-51-like kinase 1 (ULK1) pathway to promote protective autophagy and ULK1-dependent mitophagy. Thus, the combined inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
0
22
0
1
Order By: Relevance
“…SBI-0206965 and MRT-68921 are inhibitors of a serine/threonine kinase, ULK-1, which can prevent autophagosome formation, and can inhibit several additional kinases 29 . Chen et al reported that in addition to ULK1, MRT-68921 can inhibit NUAK family SNF1-like kinase 1 (NUAK1), an anti-oxidant molecule, and eventually can exert effective cytotoxicity in various solid cancer cell lines 30 . Moreover, Hwang et al recently reported that both SBI-0206965 and MRT-68921 could induce degradation of internal tandem duplication mutations in the FLT3 tyrosine kinase receptor (FLT3-ITD) protein, thereby exerting cytotoxicity in FLT-ITD AML cells 31 .…”
Section: Discussionmentioning
confidence: 99%
“…SBI-0206965 and MRT-68921 are inhibitors of a serine/threonine kinase, ULK-1, which can prevent autophagosome formation, and can inhibit several additional kinases 29 . Chen et al reported that in addition to ULK1, MRT-68921 can inhibit NUAK family SNF1-like kinase 1 (NUAK1), an anti-oxidant molecule, and eventually can exert effective cytotoxicity in various solid cancer cell lines 30 . Moreover, Hwang et al recently reported that both SBI-0206965 and MRT-68921 could induce degradation of internal tandem duplication mutations in the FLT3 tyrosine kinase receptor (FLT3-ITD) protein, thereby exerting cytotoxicity in FLT-ITD AML cells 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chen et al. demonstrated that simultaneous inhibition of ULK1 (MRT68921) with NUAK1 (also known as ARK1) induces apoptosis in various cancer types ( 31 ).…”
Section: Impact Of Inhibiting the Initiation And Nucleation Steps Onmentioning
confidence: 99%
“…MAPK1/3 kinase-dependent ULK1 degradation attenuated mitophagy [ 29 ]. Moreover, antioxidant therapy induced elevated ROS levels to activate ULK1 pathway to promote protective autophagy and ULK1-dependent mitophagy [ 30 ]. However, how the ULK1 complex is regulated to trigger mitophagy induction is not clear.…”
Section: Discussionmentioning
confidence: 99%